A novel single-phase γ′ nanocrystalline coating with high resistance to oxidation and scale rumpling yet mitigated interdiffusion with the alloy substrate. (November 2021) - Yang, Shasha; Li, Shuai; Wang, Jinlong; Bao, Zebin; Yang, Lanlan; Chen, Minghui; Zhu, Shenglong; Wang, Fuhui
Abstract: Novel single-phase γ′ nanocrystalline coatings with and without Pt modification were developed on René N5 single-crystal superalloy to investigate their cyclic oxidation behaviors at 1100 °C and 1150 °C. Compared with conventional β-(Ni, Pt)Al coating, the γ′ nanocrystalline coatings, whether with Pt addition or not, prevailed in terms of inhibiting elements interdiffusion and surface rumpling. More importantly, Pt introduction was observed to further enhance oxidation performances of the γ′ nanocrystalline coating. The synergistic effect of nanocrystalline structure and Pt modification promoted to develop a highly purified alumina scale, preventing the formation of extensive Y-rich oxide impurities and avoiding the premature failure of TGO. Graphical Abstract: ga1 Highlights: A novel single-phase γ′ nanocrystalline coating with high oxidation resistance is prepared. Pt introduction in the γ′ nanocrystalline coating facilitates forming purified oxide scale free of oxide impurities. The γ′ nanocrystalline coating exhibits high rumpling resistance. The degradation of the γ′ nanocrystalline coating is successfully alleviated by Pt addition.